Measurement of charged-particle multiplicity distributions and their Hq moments in hadronic Z decays at LEP - Dova, María Teresa (2003)
The charged-particle multiplicity distribution is measured for all hadronic events as well as for light-quark and b-quark events produced in e+e− collisions at the Z pole. Moments of the charged-particle multiplicity distributions are calculated. The Hq moments of the multiplicity distributions are studied, and their quasi-oscillations as a function of the rank of the moment are investigated.